2020
DOI: 10.1039/d0ra03672b
|View full text |Cite
|
Sign up to set email alerts
|

Developments and applications of nanomaterial-based carbon paste electrodes

Abstract: This review summarizes the progress that has been made in the past ten years in the field of electrochemical sensing using nanomaterial-based carbon paste electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 233 publications
0
64
0
Order By: Relevance
“…According to some studies, function of the modied electrodes is basically dependent on the modier features, which is utilized in the modication procedure. [43][44][45] In addition, adjustment of the electro-chemical sensor, which use the conductive mediators like nanomaterials, ionic liquid (IL), and conductive polymers can cause assessing the biological specimens and medicines at the nanomolar level. [46][47][48]…”
Section: Electrochemical Sensing Modified Electrodesmentioning
confidence: 99%
“…According to some studies, function of the modied electrodes is basically dependent on the modier features, which is utilized in the modication procedure. [43][44][45] In addition, adjustment of the electro-chemical sensor, which use the conductive mediators like nanomaterials, ionic liquid (IL), and conductive polymers can cause assessing the biological specimens and medicines at the nanomolar level. [46][47][48]…”
Section: Electrochemical Sensing Modified Electrodesmentioning
confidence: 99%
“…The CPs have charge mobility along with their p-electron backbones that handle their uncommon electronic features such as lower energy optical transition, better electrical conductivity, higher surface area, high electron affinity, and mechanical exibility. [22][23][24][25][26][27][28] The most effective parameters constructing the physical properties of CPs are conjugation length, degree of crystallinity, and intra-and interchain interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A carbon paste electrode (CPE) was selected for modication because it is cheap, can be reproducibly fabricated in any laboratory and SiO 2 -GOQDs can be easily integrated into the electrode. 31 Two antibiotics and two hormones were selected for investigation, namely: sulfamethoxazole and trimethoprim, diethylstilbestrol and estriol (Fig. 1).…”
Section: Electrochemical Properties Of the Carbon Paste Electrode Modmentioning
confidence: 99%
“…25 Various materials have been used as working electrodes in such devices: conductive glasses, 26 screen-printing, 27 glassy carbon, 28 ceramic carbon, 29 and carbon paste. 30,31 To increase the electroactive area and facilitate the kinetics of the electrode/solution interface, the electrodes have usually been modied with metal/ metal oxide nanoparticles, 32,33 carbon nanotubes, 34 graphene or GO, 18,35 or with hybrid silica-based materials. 36 For example, it was found that the addition of mesoporous silica (SBA-15) to a carbon paste electrode (CPE) can considerably enhance its sensitivity toward diethylstilbestrol, 37 by as much as immobilization of graphene on glassy carbon electrode.…”
Section: Introductionmentioning
confidence: 99%